Optical and experimental evaluation of a directly irradiated solar reactor for the catalytic dry reforming of methane - Tayseir M. Abdellateif (17380381) (2023)
Dry reforming of methane is a process to produce syngas which is a major precursor for many chemicals and ultra-clean fuels. It is a CO2-assisted process that leads to the conversion of CO2 to higher-value products but is also a highly endothermic process that requires significant amounts of energy in the form of CO2 emitting fuels. For these reasons, this study focused on the direct utilization of concentrated solar energy by irradiating the catalyst directly rather than via a heat transfer fluid or conductive heat transfer. In addition, it uniquely adopts a tubular reactor with transparent (quartz) walls configuration, which allows extending the length of the irradiated (hot) zone to control the residence time. The new reactor was designed using Monte-Carlo ray-tracing modeling and evaluated experimentally using a commercial Ni-based catalyst. In brief, the reacting gas mixture (CH4:CO2 − 5 %: 5 %) was fed into the reactor at weight gas hourly space velocities of around 17–58 l h−1 g−1 and three different temperature levels (550 °C, 650 °C, and 800 °C). Although the non-conventional mode of heating, the achieved methane conversions (∼93 % at 800 °C to ∼ 53 % at 550 °C) and H2 / CO ratios (∼0.9 at 800 °C to ∼ 0.4 at 550 °C) were similar to literature studies with the same catalyst. At the same time, the quartz walls showed no degradation after more than 80 h of intermittent testing. On the other hand, the overall energy efficiency was estimated to be less than 1 %, considering the radiation intercepted by the reactor system. However, it rose to 5 % − 25 % when correcting for the actual amount of irradiance on the catalytic bed. Other Information Published in: Chemical Engineering Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cej.2022.139190